Age-related changes in shorea dasyphylla fowx. growth and physiology - Simol, Ira Carlbrenie (2021)
Shorea dasyphylla Foxw. is an important indigenous timber species in Malaysian forestry. In recent years, initiation of restoration programmes using indigenous tree species such as S. dasyphylla is due to continued demand of tropical timbers, especially dipterocarps. However information regarding age-related change in tree growth and physiology is scarce. This study was specifically conducted to assess the growth performance of Shorea dasyphylla trees at different stand ages through its physiological and morphological measurements. The study plots were located at the Universiti Putra Malaysia–Mitsubishi Forest Restoration project area of Universiti Putra Malaysia Bintulu, Sarawak Campus. Plots of 300 m2 were selected, representing stands of different ages namely 1- (P1), 9- (P9), 14- (P14), and 20- (P20) years old. Four S. dasyphylla trees or seedlings were selected from in each plot for the study. Tree morphology measurements were assessed every six months for a period of 18 months. On the other hand, the morphology and physiology properties of the leaves as well as the soil properties were also determined. Both total height and diameter breast height growth showed a sigmoid trend as the tree aged. P9 recorded the slowest total height increment pace than the other three stands. P1 focused on both shoot apical meristem growth, especially in the third measurement interval, whereas P20 focused primarily on radial growth. In the third measurement interval of the study (after one year), a significant height increase in P1 was seen, which was most likely due to the well-established root systems that let these seedlings absorb more soil moisture and nutrients. Apart from that, the leaf area, width, length, thickness and chlorophyll content showed significant increment as the tree aged. P1 stand was also observed to have narrow, short and thin leaves compared to both canopy layers of the older stands (P14 and P20). The transpiration rate in P1 leaf was the highest, which then linearly declined over time. No significant difference was observed for leaf stomatal density in all stand age. The photosynthetic rate and stomatal conductance increased gradually until they reached their peak ages (12 to 18 years and 14 years respectively) and the decline continuously over time with a clear polynomial trend. There was no significant relationship identified between leaf N concentration and stand age. P9 recorded the lowest leaf N while the highest was recorded by P14. A constant decrease in P content was found in the leaf over time with polynomial trend. The leaf K, Mg and Ca content shared a similar trend where the value decreased until a certain age 14 years (K), 9 years (Mg) and 9 years (Ca) respectively before they started to increase afterward. Soil available P and exchangeable Mg showed reduction in values with increasing stand age as these nutrients were greatly consumed for tree growth. The value of soil exchangeable K declined until year 10 before it started to increase with a polynomial association. The soil exchangeable Ca increased exponentially with time and significantly higher value was recorded by the oldest stand. The overall results suggested that age does influence the growth, and leaf morphological and physiological development of S. dasyphylla.